Student Experiences in Accessing Learning Higher Education During Covid-19: Case of a University in Malawi - Banda, T. (South African Journal of Higher Education, 2022)
In 2020, the world experienced the unexpected as the Covid-19 pandemic ravished countries across the globe. This led to major disruptions in people’s day to day lives. Within the education sector, schools and other institutions of learning were forced to shut down. One way of regaining some semblance of normality involved teaching and learning taking on a different format as institutions migrated to online teaching. Alongside this transition came major adjustments that both institutional staff and students had to make. While the transition from face-to-face learning to online was argued to have been an uphill struggle, the situation varied from country to country and region to region, with most countries especially in the Global North, to a large extent, transitioning with reasonable ease. The transition to online learning in response to Covid-19 offered an opportunity to clarify aspects that influence the use of digital technology in teaching and learning as well as to explore the overall student learning experience. The main objective of the article is to explore how students in Malawi, a country in the Global South and one of the poorest countries in the world, coped with this major disruption in trying to access higher education. Using a qualitative approach, data was collected through interviews with both undergraduate and postgraduate students. Data was analysed thematically, and findings presented based on themes emerging from the analysis that were categorised as pre-lockdown, lockdown and post-lockdown experiences. Findings revealed the interconnectedness between the various aspects of student life that affect their learning experiences. It also highlighted how disruption only bring to the fore underlying issues from where learning experiences would either be looked at as positive or negatives.